Distribution of bacteria in different regions of the small intestine with Zanthoxylum bungeanum essential oil supplement in small-tailed Han sheep - Zhang, Hailong; Lang, Xia; Zhang, Yanshu; Wang, Cailian (Frontiers in Microbiology, 2022)
Background: Ruminant gastrointestinal tract microorganisms are important in improving host health and productivity. However, because most recent studies concentrate on the rumen, a thorough understanding of the structure and function of microbial communities is lacking. Zanthoxylum bungeanum essential oil (EOZB), an extract of a conventional Chinese herbal medicine, provides many benefits. However, how EOZB controls ruminant gut microbiota is not fully understood. In this study, to better understand how EOZB affects the distribution of bacteria throughout the small intestine, different doses of EOZB were added to the diets of small-tailed Han sheep (STH) and high-throughput 16S rRNA gene was used to examine 60 samples from the duodenum, jejunum, and ileum. Results: In horizontal and vertical investigations of bacteria in the small intestine, different EOZB doses had substantial effects on phyla and genera of bacteria in the same location in the small intestine of STHs. At the same dose of EOZB, the five most abundant genera of bacteria varied in different regions of the small intestine. Such differences in composition of bacteria could determine how nutrients were digested and absorbed as well as host gut health. The results substantially advance the current state of knowledge of bacterial dispersion profiles in the small intestine of STH and also the effects of EOZB on those profiles. Conclusions: The EOZB favorably affected the bacterial dispersion status in the STH small intestine. The research provides new information for potential herbal applications in ruminant production as well as how to improve the distribution of bacteria in the small intestine of ruminants. Additionally, it offers a theoretical foundation for the creation and use of microecological formulations as well as the choice of probiotics for ruminants.